REPRESENTASI FEMINISME DALAM FILM JANE EYRE (2011): STUDI ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE - Rima Sarah (Fakultas Ilmu Budaya, Universitas Jambi, 2021)
This study aims to represent feminism in a film entitled Jane Eyre through elements of Charles Sanders Peirce's Theory of Semiotics. The science of Semiotics used in this study serves as a basis for interpreting the signs found into a clear meaning. By using descriptive qualitative method, the researcher analyzes signs that contain hidden meanings in Jane Eyre's film, which is based on a novel with the same title by Charlotte Bronte. The researcher uses the data found in the film and then analyzes it to be able to interpret it using Pierce's Semiotic Theory. The subject of this research is the Jane Eyre film with the object of research being the scenes which represent the feminism of the main character Jane Eyre. The results of the research conducted, researchers found the meanings of representation of feminism that can be interpreted through the characters, scenes, and properties used in the film. The conclusion of this study is the representation of feminism in the Jane Eyre film which is reflected in the main character Jane Eyre.